The Maxwell Demon: a proposal for modeling in ecological synthesis in art practices (Música Hodie, 2018)
This paper aims to expand the research on ecological synthesis models (KELLER, 1999) through the inclu- sion of improvisation practice. We propose a formalization of creative processes in sonic improvisatory-compositio- nal environments (targeting comprovisation), based on ecologically grounded creative practices. Our approach en- tails the use of socio-ecological models that deal with complex adaptive systems [SIBERTIN et al., 2011]. We develo- ped a performance/experiment called The Maxwell Demon, as a case study. The observations done during the study indicate that imitation is an important strategy for creative activities in socio-ecological systems. Improvisation may provide a relevant sonic content in ecological environments, enhancing their flexibility without losing consistency. Keywords: Comprovisation; Socio-Ecological System; Performance/Experiment